Molecular characterisation of influenza B virus from the 2017/18 season in primary models of the human lung reveals improved adaptation to the lower respiratory tract - Duygu Merve Çalışkan; Sriram Kumar; Saskia Hinse; Klaus Schughart; Rainer Wiewrodt; Stefan Fischer; Vera Krueger; Karsten Wiebe; Peter Barth; Alexander Mellmann; Stephan Ludwig; Linda Brunotte (Emerging Microbes and Infections)
The 2017/18 influenza season was characterized by unusual high numbers of severe infections and hospitalizations. Instead of influenza A viruses, this season was dominated by infections with influenza B viruses of the Yamagata lineage. While this IBV/Yam dominance was associated with a vaccine mismatch, a contribution of virus intrinsic features to the clinical severity of the infections was speculated. Here, we performed a molecular and phenotypic characterization of three IBV isolates from patients with severe flu symptoms in 2018 and compared it to an IBV/Yam isolate from 2016 using experimental models of increasing complexity, including human lung explants, lung organoids, and alveolar macrophages. Viral genome sequencing revealed the presence of clade but also isolate specific mutations in all viral genes, except NP, M1, and NEP. Comparative replication kinetics in different cell lines provided further evidence for improved replication fitness, tolerance towards higher temperatures, and the development of immune evasion mechanisms by the 2018 IBV isolates. Most importantly, immunohistochemistry of infected human lung explants revealed an impressively altered cell tropism, extending from AT2 to AT1 cells and macrophages. Finally, transcriptomics of infected human lung explants demonstrated significantly reduced amounts of type I and type III IFNs by the 2018 IBV isolate, supporting the existence of additional immune evasion mechanisms. Our results show that the severeness of the 2017/18 Flu season was not only the result of a vaccine mismatch but was also facilitated by improved adaptation of the circulating IBV strains to the environment of the human lower respiratory tract.